Incremento De La Operatividad De Las Maquinas De La Empresa Metal Work Industrias Sac Mediante Un Plan De Gestion De Mantenimiento Preventivo - Diestra Galdos, Hagler Marco (2017)
This research work is based on the management of a preventive maintenance plan for the machines of the workshop of the Metal Work Industrias SAC, with the purpose of minimizing failures due to lack of maintenance in them, increasing in this way the performance of the Productive system of the company. To achieve this objective, a field modality was used, which consisted of the collection of direct information and descriptive and documentary type, of the 25 machines with which the company has its different areas. A Pareto analysis was applied to the total of the machines, resulting eight of them in critical condition due to a greater number of failures and times of repair. It is then that the preventive maintenance plan was elaborated, which specifies the realization of periodic activities, which serve as an aid to its optimal functioning, also creating control tools to guarantee the effectiveness of the preventive maintenance management system. Then the maintenance indicators were calculated, comparing the results before and after applying the preventive maintenance plan, in order to provide the company with a tool to monitor the operational performance of the machines. Finally, the economic feasibility of the implementation of the preventive maintenance plan was evaluated, demonstrating the reduction of costs for unplanned maintenance, which in turn brings benefits and avoids delays in the production process, satisfying the needs of the company.